Cardiac injury caused by iron overload in thalassemia - Fu, Chunxi; Yang, Xue (Frontiers in Pediatrics, 2025)
Cardiac iron overload affects approximately 25% of patients with β-thalassemia major, which is associated with increased morbidity and mortality. Two mechanisms are responsible for iron overload in β-thalassemia: increased iron absorption due to ineffective erythropoiesis and blood transfusions. This review examines the mechanisms of myocardial injury caused by cardiac iron overload and role of various clinical examination techniques in assessing cardiac iron burden and functional impairment. Early identification and intervention for cardiac injury and iron overload in β-thalassemia have the potential to prevent and reverse or delay its progression in the early stages, playing a crucial role in its prognosis.